Long tail fibres of the novel broad‐host‐range T‐even bacteriophage S16 specifically recognize Salmonella OmpC. Issue 4 (15th January 2013) - Marti, Roger; Zurfluh, Katrin; Hagens, Steven; Pianezzi, Jasmin; Klumpp, Jochen; Loessner, Martin J.
Summary We report isolation and characterization of the novel T4‐like Salmonella bacteriophage vB_SenM‐S16. S16 features a T‐even morphology and a highly modified 160 kbp dsDNA genome with 36.9 mol % G+C, containing 269 putative coding sequences and three tRNA genes. S16 is a virulent phage, and exhibits a maximally broad host range within the genus Salmonella, but does not infect other bacteria. Synthesis of functional S16 full‐length long tail fibre (LTF) in Escherichia coli was possible by coexpression of gp37 and gp38. Surface plasmon resonance analysis revealed nanomolar equilibrium affinity of the LTF to its receptor on Salmonella cells. We show that OmpC serves as primary binding ligand, and that S16 adsorption can be transferred to E. coli by substitution of ompC with the Salmonella homologue. S16 also infects 'rough' Salmonella strains which are defective in lipopolysaccharide synthesis and/or its carbohydrate substitution, indicating that this interaction does not require an intact LPS structure. Altogether, its virulent nature, broad host range and apparent lack of host DNA transduction render S16 highly suitable for biocontrol of Salmonella in foods and animal production. The S16 LTF represents a highly specific affinity reagent useful for cell decoration and labelling, as well as bacterial immobilization and separation.